Controlling a Medical Wheelchair by Voice Commands and Improving its Response Using a Fuzzy Proportional-Integral-Derivative Controller - احمد, احمد (Latakia University Journal -Engineering Sciences Series, 2021)
Informatics and computer technologies, with different specializations, constitute an essential component of medical engineering systems for rehabilitation, especially those related to paralysis and lower limb amputations. One of the applications of informatics technology is to improve human-machine interaction systems so that it provides wireless control with any electronic system aimed at helping people with special conditions such as those with amyotrophic lateral sclerosis, in order to avoid the need for human intervention. This research aims to harness informatics techniques in controlling a designed electric wheelchair, by the possibility of controlling it through voice commands received by an Android application, and then sent wirelessly to the NodeMCU chip. The application showed a high degree of patient satisfaction. The Fuzzy-PID controller algorithm has also been implemented in order to ensure a high response speed and great accuracy, so that the chair movement does not pose a threat to the patient’s life, in terms of exceeding the required movement, in addition to ensuring smooth take-off. The results also illustrated that the Fuzzy-PID control principle showed a very good time response compared to the conventional PID controller, in addition to eliminating the overshooting case.